2022
DOI: 10.3390/jcm11113136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mindfulness-Based Stress Reduction on the Well-Being, Burnout and Stress of Italian Healthcare Professionals during the COVID-19 Pandemic

Abstract: COVID-19 has overwhelmed healthcare systems and increased workload and distress in healthcare professionals (HCPs). The objective of this study was to evaluate baseline distress before and after the pandemic, and the effect of Mindfulness-Based Stress Reduction (MBSR) training on well-being (PGWBI), stress (PSS) and burnout (MBI) in Italian HCPs. Moreover, the “fear of COVID-19” (FCV-19S) questionnaire was administered to HCPs participating in the post-emergency MBSR program. Baseline distress results were mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
(52 reference statements)
1
10
0
Order By: Relevance
“… Li et al (2020) listed a growing body of research on general negative impacts that COVID-19 posed on mental health but they highlighted that this academic literature mostly fell between the two camps of being either commentaries or cross-sectional studies. Linking the expanded requirement for mindfulness to COVID-19, whilst relying on pre-COVID research, is consistent with other laudable work which also acknowledges that the bona fide research prior to 2019 has relevance to the pandemic and post-pandemic era ( Tement et al, 2021 ; Marotta et al, 2022 ; Sampei et al, 2022 ). These writings also tacitly acknowledge the paucity of published work in the last 3 years that provide concurrent academic sources.…”
Section: Methodssupporting
confidence: 72%
“… Li et al (2020) listed a growing body of research on general negative impacts that COVID-19 posed on mental health but they highlighted that this academic literature mostly fell between the two camps of being either commentaries or cross-sectional studies. Linking the expanded requirement for mindfulness to COVID-19, whilst relying on pre-COVID research, is consistent with other laudable work which also acknowledges that the bona fide research prior to 2019 has relevance to the pandemic and post-pandemic era ( Tement et al, 2021 ; Marotta et al, 2022 ; Sampei et al, 2022 ). These writings also tacitly acknowledge the paucity of published work in the last 3 years that provide concurrent academic sources.…”
Section: Methodssupporting
confidence: 72%
“…For instance, they can arrange regular seminars, conferences, and workshops at the workplace to provide approaches for personal growth for medical staff to enhance their resilience, which can further decrease their depressive symptoms, as proved in this study. Moreover, stress management and structured resilience training programs such as Stress Management and Resiliency Training (SMART) [ 76 ] and Mindfulness-Based Stress Reduction (MBSR) [ 77 ] can be enacted to prepare medical workers to deal with challenges and difficulties they will encounter. In addition, hospital managers should provide comprehensive counseling and support services for the medical staff as much as possible to help them reduce depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline levels of compassion fatigue and stress in both groups are average values, comparable to those found in other similar studies [ 5 , 10 , 56 ]. In a recent and interesting study in Italian healthcare professionals evaluating baseline stress levels before and after the pandemic and the effect of Mindfulness-Based Stress Reduction (MBSR) training on well-being (PGWBI), stress (PSS), and burnout (MBI), the authors concluded that MBSR training may represent an effective strategy to reduce distress in an emergency period [ 57 ]. Although the type of intervention used in this study had a different approach, the results are similar to our study.…”
Section: Discussionmentioning
confidence: 99%